STURKTUR DAN FUNGSI SOSIAL KEPERCAYAAN MASYARAKAT DI NAGARI SUNGAI ASAM SICINCIN KECAMATAN 2X11 ENAM LINGKUNG KABUPATEN PADANG PARIAMAN - Isyatil Mardiah; Wirsal Chan; Amril Amir (Jurnal Bahasa dan Sastra, 2013)
The purpuse  of research is structure description and social function faith community built new house in Sungai Asam Sicincin Kecamatan 2x11 Enam Lingkung Kabupaten Padang Pariaman. The research is kualitatif research of deskriptif method. Accommodate data and do with observation, interview, take direct words from informan and record again the result. Based of research conclusion that idiom faith communication on convey their love and feel on figuratife language. Sosial function of faith find on this research are four parts and idiom structure are two part of structure and three part of structure.